The prevalence of mechanical low back pain among proprioceptive neuro muscular facilitation and core muscle stabilisation - Thirunavukkarasu, M. J.; Kumar Das, Bikash; Vrushabhendra, H. N. (International Journal Of Community Medicine And Public Health, 2017)
Background: Cervical radiculopathy is a common disorder causing pain and disability. Objective was to determine the effects of mechanical versus manual traction in manual physical therapy combined with segmental mobilization and exercise therapy it the physical therapy management of patients with cervical radiculopathy. Methods: The mechanical and manual traction was applied in group A and B along with common intervention of segmental mobilization and exercise therapy in both groups for 5 weeks. The outcomes were assessed by NPRS and NDI at the baseline and after completion of 5 weeks exercise program at 3 days per week. The paired and unpaired t test was applied at 95% confidence interval to determine the statistical difference among two groups and data was analysed by SPSS software version-23. Results: The result revealed that there was statistically both mechanical and manual traction techniques are equally significant in group A and B for pain and disability (p <0.05) and were better in the experimental group. Conclusions: If patients of cervical radiculopathy treated with mechanical traction, segmental mobilization and exercise therapy will manage pain and disability more effectively than treated with manual traction, segmental mobilization and exercise therapy.